CLINICAL AND EPIDEMIOLOGICAL FEATURES OF 210 COVID-19 PATIENTS IN BABYLON GOVERNORATE DURING 2020 - Nawar Al-Janabi; Mohanad Jawad; Abbas abed Sharhan; Zahraa M. Madani; Maher Jawad; Mohammad Agresh (Scholar Express Journals, 2021)
Coronavirus infection has become a major public health concern. Many studies have reported the clinical and epidemiological features of Coronavirus Disease 2019 (COVID-19), but the data remained inconsistent. This study aimed to study more available data to provide clearer picture to understand the characteristics of coronavirus patients. A total of 210 confirmed Covid-19 patients were included in this study. Data were collected during March 25th to June 24th and the impact of age, comorbidities, gender, contact, travel history, job title, contacts, on the dynamic profile of signs and symptoms in Covid-19 patients were investigated. Results showed that the patients in the age range of <10 - 29 years were mostly asymptomatic. Mild and severe symptoms were the most common in patients aged from 29 to 59 years. (10.63%) of patients aged from 60 to 69 years were asymptomatic and (5.66%), (2.70%), (3.84%) of patients were falling with the simple, mild symptoms, and sever symptoms respectively. Additionally, results showed that there was a significant difference between patients without comorbidities and the severity of COVID-19 infection. Also, there was a substantial association (p >< 0.000) between individuals’ contacting confirmed COVID-19 patients and the incidence of infections. In summary, the clinical and epidemiological features of Covid-19 patients were non-specific and heterogeneous. The information provided in this study important for understanding the impact of Covid-19
Keywords: Covid-19; Pandemic; Comorbidities; Age